Answer:
f(2) = 12
f(x) = 7, x = -3, 1
Step-by-step explanation:
<u>a)</u>
plug in x as 2
f(x) = 2^2 + 2(2) + 4
f(x) = 4 + 4 + 4
f(x) = 12
<u>b)</u>
replace f(x) with 7
7 = x^2 + 2x + 4
x^2 + 2x - 3 (move 7 to other side)
Factor
ac: -3x^2
b: 2x
split b into 3x, -x
(x^2 -x) + (3x - 3)
↓ ↓
x(x-1) + 3(x-1)
Factor: (x-1)(x+3) = 0
Solve using Zero Product Property:
x - 1 = 0, x + 3 = 0
x = 1, x = -3
<span> Given polynomial x^2+8x-48 = 0</span>
<span>x^2+12x-4x-48 = 0</span>
<span>x(x+12)-4(x+12) = 0</span>
<span>(x+12)(x-4) = 0</span>
<span>x+12 = 0</span>
Subtract 12 from each side.
<span>x+12-12 = 0-12</span>
<span>x = -12</span>
<span>and x-4 = 0</span>
Add 4 to each side.
<span>x-4+4 = 0+4</span>
<span>x = 4</span>
<span>Roots are -12,4.</span>
You know the adjacent and you need to find the opposite, so you would use tangent. Your equation would look like this; tan 26°= x/28. You would need to multiply both sides by 28 to simplify it to this; 28*tan 26°= x
Solving this, you would get an answer of 13.7
Answer:
dddddStep-by-step explanation:
Answer:
sorry I can't know the answer